1998
DOI: 10.1038/sj.gt.3300747
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four strategies for tumour vaccination in the B16-F10 melanoma model

Abstract: We have compared four cell-based tumour vaccine strathe two latter vaccines promoted antitumour activity, tegies in prevention experiments using the B16-F10 melawhereas the vaccines consisting of B7.1-expressing noma model. Two of these are thought to favour the direct tumour cells or the hybrid vaccine failed to provide any antigen presentation pathway (B16-F10 expressing B7.1 antitumour activity. Recently human trials have comand hybrids made between B16-F10 cells and menced using transfection of the B7.1 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…1,46 In our study, the protection of vaccination with wild-type cells had a slight antitumor effect, with a survival of nearly 20% when employing 2 million cells per mouse. This observation agrees with the idea of B16 melanoma as an immunogenic tumor cell line 47 that can produce vitiligo reactions in immunized animals. 48 Almost all the animals in our experiment had vitiligo on the snout, but some also developed a high vitiligo reaction over the rest of the body.…”
Section: Discussionsupporting
confidence: 92%
“…1,46 In our study, the protection of vaccination with wild-type cells had a slight antitumor effect, with a survival of nearly 20% when employing 2 million cells per mouse. This observation agrees with the idea of B16 melanoma as an immunogenic tumor cell line 47 that can produce vitiligo reactions in immunized animals. 48 Almost all the animals in our experiment had vitiligo on the snout, but some also developed a high vitiligo reaction over the rest of the body.…”
Section: Discussionsupporting
confidence: 92%
“…Specificity of the allogeneic cell vaccine Allogeneic vaccine K1735-M2 (H-2k) is known to confer protection against the syngeneic B16-F10 (H-2b) tumour 8,18 (Figure 1a), whereas the autologous vaccine B16-F10 is ineffective (P = 0.0021). The specificity of this unmodified vaccine was investigated in two ways: first, as this cellular vaccine was derived from C3H/HeN mice, C57BL/6J mice were vaccinated with C3H/HeN allogeneic fibroblasts that were not expected to express any tumour antigens.…”
Section: Resultsmentioning
confidence: 99%
“…Using the B16-F10 (H-2b) melanoma model, we have shown that allogeneic vaccine K135-M2 8,18 (H-2k) induced a response that was specific and dependent on both CD4+ve and CD8+ve T cells. We then genetically modified the allogeneic vaccine cells to secrete GM-CSF and show their anti-tumour efficacy against established tumour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Making autologous cancer vaccine treatments, however, is labour intensive, expensive and has too many variables for the approach to be truly characterized as a therapeutic product. Several studies have suggested that allogeneic cell lines may be able to replace this approach with a reproducible product, and the initial fear that allogeneic cell line approaches would not be as good as autologous has been demonstrated to be unfounded, as allogeneic cells can often produce better responses than autologous cells in preclinical models [4][5][6]. This only occurs in the presence of shared antigens and has been most clearly demonstrated in melanoma-based models.…”
mentioning
confidence: 99%